Pistol and rifle performance: Gender and relative age effect analysis - Mon-López, D.; Tejero-González, C. M.; de la Rubia Riaza, A.; Lorenzo Calvo, J. (International Journal of Environmental Research and Public Health, 2020)
Background: The sport overrepresentation of early-born athletes within a selection year is called relative age effect (RAE). Moreover, gender performance differences depend on the sport. The main objectives of the study were to compare performances between gender and RAE in precision shooting events. Method: The results of 704 shooters who participated in the most recent World Shooting Championship were compared. Performance was analysed by event (rifle and pistol), gender and category (junior and senior), together with RAE and six ranges of ranking positions. Results: The results of the study indicated that men scored higher than women in pistol events and that no performance differences were found in rifle events when the whole group was compared. According to the birth trimester, no significant differences were found in the participant`s distribution, nor in performance in any case. Conclusions: The main conclusions of the study are: (1) the men`s pistol performance is better than the women`s even though RAE is not associated to the shooting score in any case; (2) men and women performed equally in the general analysis, but their performances were different depending on category and event with no RAE influence.